Medication Cost Savings in Hospice and Palliative Care Through Implementation of a Quick-Reference Medication Guide - Sabol, Brittney (My University, 2022)
Symptom management is an integral component of end-of-life care provided by hospice services. This project employed a list of alternative low-cost medication options for symptom management to decrease medication costs to the hospice organization. This project applied a multifaceted educational approach to lower the average overall medication cost and the average nonformulary medication cost per patient per day. A quick-reference guide was created and comprised of a target medication list of high-cost, high-use medications, and medications proposed by the nursing and pharmacy staff. In collaboration with the organization’s pharmacy team, a list of low-cost alternative and formulary options with cost comparisons was defined for each target medication and included in the guide. All nursing staff was educated regarding the quick-reference guide and its use. The tools were disseminated physically and digitally to all home care and hospice house nurses and providers. Post-implementation data showed an average of $2.92 cost reduction in overall medication cost and $0.35 cost reduction in nonformulary medication cost per patient per day. These findings compute to a projected estimated annual savings of $149,212 to $159,870 for overall medication cost and $17,885 to $19,162 for nonformulary medication cost, dependent upon patient census. These findings support the use of a multifaceted educational approach to medication cost reduction in the hospice setting. However, further investigation of other methods is warranted, and more robust studies are needed to fully estimate the long-term impact of a project like this.
Keywords: cost savings, medication cost, educational intervention, formulary, hospice